Comunicação interna, diferenciação, integração e fragmentação na cultura organizacional em uma instituição particular de ensino superior - Tegoni, Andréia Cristina (2015)
The university Brazilian scene has undergone significant changes in recent times, especially in the private higher education. Note that in addition to the expansion of private institutions, the system is organized in a very professional manner, focused on the market and looking for short-term results. In this sense, it is assumed that the communication processes are important for the management of educational processes, especially internal communication processes. However, when talking about internal organizational communication, the analysis can be applied to a level considered even more comprehensive, the organizational culture.Studies of organizational culture are conducted, according to Martin (2001), considering three perspectives: integration, differentiation and fragmentation. These perspectives are differentiated mainly by the degree of consensus among the members of the organization about the cultural events. This implies that even before an internal communication to adopt "uniform" procedures, the degree of consensus of individuals and groups about cultural events (largely due to the communication processes) shows variations among themselves. This study aimed to analyze the three perspectives of differentiation, integration and fragmentation are present in the manifestations of organizational culture of an institution of higher education, particularly from its internal communication.The research method adopted was the only case study with qualitative and exploratory approach. Data were collected from document analysis, semi-structured interviews and participant observation. The results achieved responded to the research problem and show that this study points out the manifestation of the triad of prospects for Martin (2001) occurring simultaneously, thus making the complex culture of IES. In this sense, the new studies addressing the organizational culture is suggested, using other theoretical models, as well as the replication of this study in other higher education institutions or a comparative study between two or more institutions.